The Association between 25-(OH)D Level and Metabolic Control Status in Children with Type 1 Diabetes Mellitus at Dr. M. Djamil General Hospital Padang - Dini Anggini; Eka Agustia Rini; Finny Fitry Yani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Type 1 diabetes mellitus (T1DM) is an autoimmune disease causing the destruction of pancreatic beta cells. This is an incurable condition, but with good metabolic control, an optimal quality of life can be achieved. Glycated hemoglobin (HbA1C) is still considered a reliable parameter of metabolic control. Studies showed vitamin D has a role in controlling glycemic homeostasis in children with T1DM. Calcidiol or 25-(OH)D is the best parameter to determine the level of vitamin D in the blood. This study aimed to evaluate the association between 25-(OH)D with metabolic control status in T1DM children at Dr. M. Djamil General Hospital Padang. Methods. A cross-sectional study was conducted on 43 pediatric patients with T1DM from July 2019-January 2021. Serum levels of 25-(OH)D were measured by direct CLIA method and classified into deficiency (≤ 20 ng/mL) and insufficiency (21–30 ng/mL). The HbA1C levels were calculated using the HPLC method and classified into good (<7%), adequate (7-8%), and poor (>8%) control. The Chi-square test and ANOVA were used for data analysis. The P-value of < 0.05 was considered statistically significant. Results. The majority of respondents were girls (53.5%), with 90.7% having a good nutritional status. The mean age at diagnosis was 11.25±2.85 years, and had been known to suffer from T1DM for 2.95±1.74 years. All respondents had abnormal levels of 25-(OH)D (100%), i.e., insufficiency (28%), deficiency (72%), poor (65.1%) metabolic control, and 96.4% of respondents with poor metabolic control had a deficiency of 25-(OH)D. (P-value <0.001). Conclusion. T1DM patients who have poor metabolic control have very low levels of 25-(OH)D.